Pencegahan dan Pemberantasan Korupsi: Upaya BPK dalam Bingkai Hak Asasi Manusia - Baren Sipayung; Haris Retno Susmiyati; Insan Tajali Nur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the efforts of the Indonesian Financial Audit Agency (BPK) in preventing and eradicating corruption, reviewing the BPK's main role in auditing state financial management to achieve transparency, accountability and integrity in the use of public budgets. The BPK is also involved in eradicating corruption by conducting investigative audits of suspected corruption cases and revealing facts related to the perpetrators, modus operandi and state losses. In carrying out its duties, the BPK must pay attention to the Human Rights (HAM) perspective to ensure that its efforts do not violate individual rights guaranteed by the constitution and statutory regulations. This article explores how the BPK maintains its independence to carry out objective audits and provide recommendations based on valid data. With a deeper understanding of the role of the BPK, it is hoped that this article will increase appreciation of the importance of cooperation between the BPK, government and society in overcoming corruption which undermines development and human rights principles.